2021
DOI: 10.1016/j.jcot.2020.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lower limb alignment and their effect on the functional outcome after treatment of varus degenerative OA knee by hemicallotasis using modular dynamic HTO fixator

Abstract: Medial opening wedge high tibial osteotomy (MOWHTO) Femoro tibial angle (FTA) Mechanical axis KOOS Medial compartment OA Knee Varus knee a b s t r a c tObjective: High tibial osteotomy (HTO) is an established procedure to treat medial compartmental osteoarthritis (OA) knee associated with varus deformity. It is well documented that precise correction of deformity and maintenance of correction achieved is important to ensure long term good results. This study was undertaken to record changes in radiological par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Lee et al have conducted an investigation and evaluated the influence of age on survivorship and complications after HTO, there were 41,112, 13,895 and 6138 patients underwent HTO under 60 years (Group A), between 60 and 65 years (Group B) and older than 65 years (Group C), results showed that overall revision rate was 4.2%, 6.4% and 7.3% for Group A, B, C. The 5- and 10-year revision rate and incidence of complication were significantly lower in Group A 11 . However, other studies also reported good outcomes of HTO in geriatric patients, Hrishikesh and his colleagues analyzed the functional changes of varus degenerative OA knee by hemicallotasis using modular dynamic HTO fixator, mean age of the study population in their research was 49.3 years with a maximum of 67 years, the KOOS improved from mean 56.61 preoperatively to 70.48 at the time of fixator removal, and after 1-year follow-up, KOOS score further improved significantly to 85.68 12 . It is well accepted that a mildly degenerative KOA is usually accompanied by better clinical outcomes of HTO, therefore, we performed OWHTO in patients with K–L grade up to III, and 77.6% of the OWHTO patients in our study were assessed as grade I or II of K–L grade.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al have conducted an investigation and evaluated the influence of age on survivorship and complications after HTO, there were 41,112, 13,895 and 6138 patients underwent HTO under 60 years (Group A), between 60 and 65 years (Group B) and older than 65 years (Group C), results showed that overall revision rate was 4.2%, 6.4% and 7.3% for Group A, B, C. The 5- and 10-year revision rate and incidence of complication were significantly lower in Group A 11 . However, other studies also reported good outcomes of HTO in geriatric patients, Hrishikesh and his colleagues analyzed the functional changes of varus degenerative OA knee by hemicallotasis using modular dynamic HTO fixator, mean age of the study population in their research was 49.3 years with a maximum of 67 years, the KOOS improved from mean 56.61 preoperatively to 70.48 at the time of fixator removal, and after 1-year follow-up, KOOS score further improved significantly to 85.68 12 . It is well accepted that a mildly degenerative KOA is usually accompanied by better clinical outcomes of HTO, therefore, we performed OWHTO in patients with K–L grade up to III, and 77.6% of the OWHTO patients in our study were assessed as grade I or II of K–L grade.…”
Section: Discussionmentioning
confidence: 99%